Clutch, brake, sellerator, and other stories - Foo, Vincent H. K. (Vincent Hiap Khian) (MPH Pub. : Distributed by MPH Distributors, 2010)
Prize winning short stories in the 2009 short story writing contest of the MPH-Alliance Bank National.